Empirical Model of Poverty Alleviation in Islamic Economic Perspective: Evidence from Indonesia - Muhammad Anis; Tika Widiastuti; Najim Nur Fauziah (IAIN Padangsidimpuan, 2022)
This study aims to examine the model of poverty alleviation by analyzing several aspects that in Islamic economics are considered to have an effect on poverty alleviation. Using a sample of provinces in Indonesia, this study applies to panel data analysis. The novelty of this research is using more variables, including some aspects rarely discussed in previous empirical models. The results of this study indicate a significant negative effect of mandatory and charity transfer variables on the poverty level. Although using different proxies, the results of this study are in line with and confirm previous theories and empirical research regarding the effect of zakat on poverty alleviation. In addition, the variable of increasing income was also found to have a significant effect on poverty alleviation. This provides an overview for the government to be able to optimize the role of zakat and increase income to reduce poverty, for example, by integrating the distribution of ziswaf through the provision of working capital more broadly and integrated towards economic improvement and growth so that it will bring a greater multiplier effect. In addition, the results of this study also provide recommendations for researchers to complement the limitations of this study. The limitation of this study is the lack of proxies in describing aspects that become variables of poverty alleviation in Islam as a whole. Whereas in Islam, poverty and its alleviation are multidimensional things and are not limited to material aspects but also spiritual.